Electrochemical and Microbial Dissection of Electrified Biotrickling Filters - Korth, Benjamin; Pous, Narcís; Hönig, Richard; Haus, Philip; Corrêa, Felipe Borim; Nunes da Rocha, Ulisses; Puig, Sebastià; Harnisch, Falk (Frontiers in Microbiology, 2022)
Electrified biotrickling filters represent sustainable microbial electrochemical technology for treating organic carbon-deficient ammonium-contaminated waters. However, information on the microbiome of the conductive granule bed cathode remained inexistent. For uncovering this black box and for identifying key process parameters, minimally invasive sampling units were introduced allowing the extraction of granules from different reactor layers during reactor operation. Sampled granules were analyzed using cyclic voltammetry and molecular-biological tools. Two main redox sites (−288±18 mV and −206±21 mV vs. SHE) related to bioelectrochemical denitrification were identified exhibiting high activity in a broad pH range (pH 6-10). A genome-centric analysis revealed a complex nitrogen food web and the presence of typical denitrifiers like Pseudomonas nitroreducens and Paracoccus versutus with none of these species being identified as electroactive microorganisms, so far. The results provide first insights into microbial structure-function-relationships within electrified biotrickling filters and underline robustness and application potential of bioelectrochemical denitrification for environmental remediation.